1982
DOI: 10.2214/ajr.138.6.1043
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic anatomy of the interlobar fissures: a study of 100 specimens

Abstract: A review of the anatomy of the interlobarfissures is based on a detailed study of 100 fixed and inflated lung specimens (50 right and 50 left lungs). The upper part of the fissural surface of the right lower lobe almost always faces in a slightly lateral direction and is usually concave; the lower part typically faces laterally but is usually convex.The upper part of the left major fissure also almost always faces laterally and is concave; but unlike the right side, the lower part usually faces medially and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…This is consistent with current knowledge that there are frequently incomplete fissures between the right upper lobe and right middle lobe. RAASCH et al [17] found that in 50 examined right lung specimens, there were incomplete fissures between the right upper lobe and right middle lobe in 44 (88%) specimens. In the CV-nonresponders group, 47% were treated in the right upper lobe.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with current knowledge that there are frequently incomplete fissures between the right upper lobe and right middle lobe. RAASCH et al [17] found that in 50 examined right lung specimens, there were incomplete fissures between the right upper lobe and right middle lobe in 44 (88%) specimens. In the CV-nonresponders group, 47% were treated in the right upper lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed autopsies were mostly performed on small numbers of lungs and the prevalence ranged from 7.1% to 46.7% (mean 21.5%), 5.6% to 39.3% (mean 24.6%), and 7.8% to 74% (mean 40.4%) for left oblique, right oblique, and horizontal fissures, respectively 2,3,7,[32][33][34][35][36][37][38][39][40][41] . In this summary, we intentionally ignored a paper by Dogan et al 40 (included in Table 1) because they assessed the incompleteness of fissures in routine forensic autopsies, leaving large parts of the lung uninvestigated.…”
Section: Prevalence Of Incomplete Fissuresmentioning
confidence: 99%
“…Thus a radiologist can explain some atypical images on chest x-rays or CT scans 3,4 . When lobectomy is performed in a patient with an incomplete interlobar fissure, there is a higher risk of air leakage 2,[4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Lobectomy or surgical removal of the diseased lung lobes is the preferred option for treating lung cancer. On CT, a fissure can have a variety of appearances [1], which makes its detection and segmentation challenging. A Snake is an energy minimizing spine guided by external constraint forces and influenced by image forces that pull it toward features such as line and edges [2].In practice, dilations and erosions are usually employed in pairs either dilation of an image followed by the erosion of the dilated result, or image erosion followed by dilation [3].…”
Section: Introductionmentioning
confidence: 99%